Carbon Nanomaterials for Targeted Cancer Therapy Drugs: A Critical Review. Issue 2 (29th August 2018) - Hosnedlova, Bozena; Kepinska, Marta; Fernandez, Carlos; Peng, Qiuming; Ruttkay‐Nedecky, Branislav; Milnerowicz, Halina; Kizek, Rene
Abstract: Cancer represents one of the main causes of human death in developed countries. Most current therapies, unfortunately, carry a number of side effects, such as toxicity and damage to healthy cells, as well as the risk of resistance and recurrence. Therefore, cancer research is trying to develop therapeutic procedures with minimal negative consequences. The use of nanomaterial‐based systems appears to be one of them. In recent years, great progress has been made in the field using nanomaterials with high potential in biomedical applications. Carbon nanomaterials, thanks to their unique physicochemical properties, are gaining more and more popularity in cancer therapy. They are valued especially for their ability to deliver drugs or small therapeutic molecules to these cells. Through surface functionalization, they can specifically target tumor tissues, increasing the therapeutic potential and significantly reducing the adverse effects of therapy. Their potential future use could, therefore, be as vehicles for drug delivery. This review presents the latest findings of research studies using carbon nanomaterials in the treatment of various types of cancer. To carry out this study, different databases such as Web of Science, PubMed, MEDLINE and Google Scholar were employed. The findings of research studies chosen from more than 2000 viewed scientific publications from the last 15 years were compared. Abstract : Carbon nanomaterials, thanks to their unique physicochemical properties, are gaining more and more popularity in cancer therapy. They are valued especially for their ability to deliver drugs or small therapeutic molecules to the tumor cells. Through surface functionalization, carbon nanostructure materials can specifically target tumor tissues, increasing their therapeutic potential and significantly reducing adverse effects of conventional therapy.